Soil amendments altered arbuscular mycorrhizal fungal communities in cadmium-contaminated vegetable fields - Li, Liang; Shi, Yanning; Xia, Wangbiao; Wang, Xiyang; Xin, Zaijun; Liao, Yingchun; Sun, Xiaoyan (Frontiers in Microbiology, 2024)
Soil amendments, including various types of fertilizers, are often used to control the uptake of heavy metals such as cadmium in cropping fields. The influence of these amendments on other members of the agroecosystem, such as arbuscular mycorrhizal fungi (AMF), remains less well investigated. Here, we established an experiment with the application of woody peat organic fertilizer and phosphate rock powder to examine its effects on AMF communities in two cadmium-contaminated vegetable crop fields (cucumber and pepper). We found that the application of phosphate rock powder enhanced soil phosphorus content, while the application of woody peat organic fertilizer enhanced soil nitrogen content, but neither influenced AMF abundance. We also found little influence of either amendment on measures of AMF diversity, except in one case where the Shannon index of diversity was lower in pepper fields amended with phosphate rock powder. We did, however, find significant shifts in the community composition and relative abundances of AMF taxa in the two vegetable fields, primarily as a result of shifts in the soil pH and nitrogen content.